Dynamic regulation of tissue fluidity controls skin repair during wound healing - Sarate, RM; Hochstetter, J; Valet, M; Hallou, A; Song, Y; Bansaccal, N; Ligare, M; Aragona, M; Engelman, D; Bauduin, A; Campàs, O; Simons, BD; et al. (Cell Press, 2024)
During wound healing, different pools of stem cells (SCs) contribute to skin repair. However, how SCs become activated and drive the tissue remodeling essential for skin repair is still poorly understood. Here, by developing a mouse model allowing lineage tracing and basal cell lineage ablation, we monitor SC fate and tissue dynamics during regeneration using confocal and intravital imaging. Analysis of basal cell rearrangements shows dynamic transitions from a solid-like homeostatic state to a fluid-like state allowing tissue remodeling during repair, as predicted by a minimal mathematical modeling of the spatiotemporal dynamics and fate behavior of basal cells. The basal cell layer progressively returns to a solid-like state with re-epithelialization. Bulk, single-cell RNA, and epigenetic profiling of SCs, together with functional experiments, uncover a common regenerative state regulated by the EGFR/AP1 axis activated during tissue fluidization that is essential for skin SC activation and tissue repair.